2018
DOI: 10.1093/jas/sky313
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the consumption of polyunsaturated fatty acids on the oxidative status of adult dogs

Abstract: The present study evaluated the alterations of the oxidative stress markers in adult dogs fed with high levels of PUFA from the mixture of soybean oil enriched with docosahexaenoic acid (DHA) and supplemented with a natural algae-based antioxidant (AOX). Twelve healthy adult (2 years old) Beagle dogs (6 males and 6 females, 11.20 ± 1.92 kg BW), were distributed in 2 completely randomized blocks design and fed with 4 experimental diets coated with 2 lipid sources: saturated (13% bovine tallow) or unsaturated (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 27 publications
0
11
0
2
Order By: Relevance
“…Moreover, we showed that the positive signal increases with the percentage of CSE, suggesting a good linearity of the method. However, the repeatability of the method is not excellent, since the CV is higher 4) and from clinically sick dogs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The control sample (serum oxidized with CSE) has been loaded on lane C. Dog serum proteins has been separated in SDS-PAGE, transferred to PVDF membrane and immunodetected with specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, we showed that the positive signal increases with the percentage of CSE, suggesting a good linearity of the method. However, the repeatability of the method is not excellent, since the CV is higher 4) and from clinically sick dogs (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19). The control sample (serum oxidized with CSE) has been loaded on lane C. Dog serum proteins has been separated in SDS-PAGE, transferred to PVDF membrane and immunodetected with specific antibodies.…”
Section: Discussionmentioning
confidence: 99%
“…In veterinary medicine, the diagnosis of sepsis is based on the direct detection of pathogens and/or on the “indirect” evaluation of the effects exerted by the pathogens on the organism (increased temperature, heart and respiratory rate, changes in the leukogram, altered serum concentration of acute phase proteins, modified serum protein electrophoresis); however, the parameters currently used to support a clinical diagnosis of sepsis are not enough sensitive and specific. To the best of our knowledge, in veterinary medicine, few studies have been developed about carbonyls, mainly to focus about OS and inflammatory conditions related to pregnancy in healthy dogs ( 11 ), associated with a diet rich in polyunsaturated fatty acids ( 12 ) or in diabetes mellitus in dogs ( 13 ) and in cats ( 14 ). Different substrates and techniques have been used to quantify PCOs and rarely a significant difference from sick and healthy animals was found, as in the study of Zini et al ( 14 ) that demonstrated an increased concentration of PCOs in the erythrocyte membranes of diabetic cats compared with control cats.…”
Section: Introductionmentioning
confidence: 99%
“…In dogs, the use of RBCs lysates and WB has been proven to be effective in the measurement of selected antioxidants and oxidants. In RBCs lysates, SOD was measured to evaluate the antioxidant response of dogs receiving a diet consisting of high polyunsaturated fatty acids [ 13 ], as well as in dogs with chronic kidney disease [ 14 ], atopic dermatitis [ 15 ], parvoviral infection [ 16 ], sarcoptic mange [ 17 ], leishmaniasis [ 18 ] and uncomplicated babesiosis [ 19 ]. In addition, reduced glutathione has been measured in RBCs lysates from dogs with renal azotemia [ 20 ] and GPx has been determined in RBCs lysates from dogs infected with Dirofilaria immitis [ 21 ] and with multicentric lymphoma [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Se han demostrado efectos benéficos en la salud de los perros por el suministro de antioxidantes en la dieta, a través de la reducción del estrés oxidativo (Baskin et al, 2000;Milgram et al, 2002; Pan et al, 2018). Incluso se ha eva-luado el efecto de otros suplementos dietarios en el estatus oxidativo de los caninos (Pacheco et al, 2018). Adicionalmente, se ha descrito la relación entre el estrés oxidativo de los perros y diferentes condiciones ambientales como restricciones sociales y espaciales, prácticas de manejo, condiciones de salud y diversas patologías (Macotpet et al, 2013; Passantino et al, 2014; Marquis et al, 2015).…”
Section: Introductionunclassified